2005
DOI: 10.1055/s-2005-871751
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration through Nerve Isografts is Independent of Nerve Geometry

Abstract: Investigators have theorized that tortuosity in nerve grafts may adversely affect nerve regeneration. This study investigated the effect of graft configuration and redundancy on regeneration across 2.5-cm rat sciatic nerve isografts. Thirty-two Lewis rats were randomized to four nerve grafting groups defined by gap distance and isograft conformation. In Group 1, grafts were interposed into a 2-cm gap, resulting in mild graft redundancy. In Groups 2 and 3, grafts were tacked in sinusoidal or omega-shaped config… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…A subsequent study demonstrated no differences at the 3-week time-point in analyzing myelinated axon counts between sensory, motor, and mixed (both motor and sensory components) autografts in a mixed nerve defect model 26 . Similarly, a large-scale study in 100 rats demonstrated equivocal results in motor, sensory, mixed nerve grafts via histomorphometric analysis at 5, 6, and 7 weeks in the tibial nerve model 27 . A potential shortcoming to the studies that demonstrated motor isograft superiority is the early endpoint, with histomorphometric analyses at three weeks after reconstruction 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study demonstrated no differences at the 3-week time-point in analyzing myelinated axon counts between sensory, motor, and mixed (both motor and sensory components) autografts in a mixed nerve defect model 26 . Similarly, a large-scale study in 100 rats demonstrated equivocal results in motor, sensory, mixed nerve grafts via histomorphometric analysis at 5, 6, and 7 weeks in the tibial nerve model 27 . A potential shortcoming to the studies that demonstrated motor isograft superiority is the early endpoint, with histomorphometric analyses at three weeks after reconstruction 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…The grafted nerves need to loop and insert into an under‐the‐skin “pocket” around the femur requiring the nerve ends to remain their original length after transection . The sigmoidal nature of this path does not interfere with regeneration . To provide control ANAs (6 cm), a 1‐cm ANA was coapted between two 2.5‐cm ANAs.…”
Section: Methodsmentioning
confidence: 99%
“…11 The sigmoidal nature of this path does not interfere with regeneration. 33 To provide control ANAs (6 cm), a 1-cm ANA was coapted between two 2.5-cm ANAs. Control ANAs contained a short ANA (1 cm) between two 2.5-cm ANAs rather than a single long (6 cm) ANA to control for possible suture line effects.…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral nerve injuries are common, with overall incidence standing at 6,250 per 100 thousand in the United States alone . Currently, research effort principally has been directed at improving functional outcome and regeneration accuracy of axons following neural anastomosis or grafting . Some studies suggested that isolation of the regenerating milieu, via ensheathment with autologous, biological, or synthetic materials, could promote axonal regeneration and improve functional outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that isolation of the regenerating milieu, via ensheathment with autologous, biological, or synthetic materials, could promote axonal regeneration and improve functional outcome. Among the variables investigated, fascicular alignment, suture type, location, techniques, neurorrhaphy orientation, and tension have been exhaustively studied to determine the optimal neurorrhaphy methods . Tensionless repair, introduction of viable Schwann cells, and delivery of certain neurotrophic agents only had modest recovery benefits .…”
Section: Introductionmentioning
confidence: 99%